Mutual promotion effect of SO2 and NOx during yellow phosphorus and phosphate rock slurry adsorption process. Issue 8 (17th February 2021) - Nie, Yunxiang; Wang, Xujun; Dai, Jinfeng; Wang, Chi; He, Dedong; Mei, Yi
Abstract: Removing SO2 and NOx released from middle and small‐scaled coal‐burning boiler is one important strategy for air pollution control. Herein, we first report a novel process on simultaneous eliminating SO2 and NOx at low temperature, by employing large scale and cheap sources of phosphorus sludge and phosphate rock slurry. The results showed that 100% desulfurization and denitrification efficiency can be obtained, and there exhibited a significant mutual‐promoting effect between SO2 and NOx abatement processes. Based on characterizations and theoretical calculation results, it was found that the active substances produced by the interaction of sulfur and nitrogen species played a significant role in promoting the removal of SO2 and NOx. Compared with traditional purification technology, this process can achieve simultaneous desulfurization and denitrification with no discharge of secondary pollutants, and can be regarded as a new and economic technology for efficient removal of SO2 and NOx in industrial scale.